Experimental study of a solar still with sponge cubes in basin - A/K Abu-Hijleh, Bassam (2003)
The performance of a solar still with different size sponge cubes placed in the basin was studied experimentally. The increase in distillate production of the still ranged from 18% to 273% compared to an identical still without sponge cubes under the same conditions. The effects of sponge cube size, percent volume of sponge, water depth, water salinity and the use of black coal and black steel cubes were also investigated. The study showed that the daily production of such a still can be greatly enhanced using sponge cubes.